PENGARUH PEMBERIAN STRETCHING DAN EDUKASI PENCEGAHAN NYERI LEHER PADA POSISI ERGONOMIS PENJAHIT DI PT GARMEN PERKASA - Sandi Akbar; Nabila Salsabillah Warasti (Jurnal Ilmiah Fisioterapi, 2025)
Backround. Ergonomics is an applied science of human biology and its relationship with engineering for workers and the work environment, in order to get maximum job satisfaction in addition to increasing its productivity, or the adjustment of work tasks to human body conditions. Counseling activities carried out to 27 tailors at PT Garmen Perkasa. Purpose. This study aimed at patient form of education on ergonomic positions when sewing and treatment in the form of neck stretching to reduce pain. The method to be used in this extension is in the form of a presentation by modeling some stretching exercises and using the Leaflet media. Reserch methods. The reserch Ergonomic position assessment using measurements with the REBA (Rapid Entire Body Assessment), performed 2 measurements, namely pre and post test. The result. sthe average REBA score obtained before counseling is 3,851 with an average action level of 1,629 and after counseling the average results are obtained average REBA score of 2.74 and an average action level of 1.529. Based on these results it was found that REBA scores after counseling had decreased by an average of 1,111 while decreases in action levels occurred in 10 tailors with an average of 0.37 from action level 2 (moderate risk) to 1 (low risk). Although the decrease in action level was only found in 10 people, the REBA score in 19 tailors had decreased. Counseling for neck pain prevention and education of ergonomic positions in PT Garmen Perkasa's tailors can reduce the risk of musculoskletal disorder, increase worker productivity, produce quality and reduce additional costs to be incurred, so that the profits derived by the company also increase. Keywords: Stretching, Neck pain, Rapid Entire Body Assessment (REBA), Ergonomic Position Education